Mechanical and biochemical properties of human articular cartilage in osteoarthritic femoral heads and in autopsy specimens. - Roberts, S; Weightman, B; Urban, J; Chappell, D (1986)
We studied the mechanical and biochemical properties of articular cartilage from 22 osteoarthritic femoral heads obtained at operation and 97 femoral heads obtained at autopsy. Cartilage from the zenith and from the antero-inferior aspect of each head was tested both in tension and in compression. Water content, swelling ability and proteoglycan content were measured, the cartilage was examined histologically and the density of the underlying bone was assessed. Fifty-five of the autopsy specimens were defined as macroscopically normal because they exhibited no progressive fibrillation patterns on staining with Indian ink; but significant changes in water content, bone density and tensile strength related to age were seen in this group. In 20 pairs of femoral heads which were both macroscopically normal, we found, surprisingly, that cartilage from the left and right sides of the same patient was sometimes very different. Compared with the normal autopsy specimens the osteoarthritic specimens had a significantly increased swelling ability, a lower proteoglycan content and impaired mechanical properties, being both weaker in tension and softer in compression. Abnormal autopsy specimens had values intermediate between those of osteoarthritic and normal groups. Results from this abnormal group suggest that there is no primary loss of proteoglycan in early osteoarthritis.